Hadits-Hadits Tahlilan: Analisis Konflik dan Nilai-Nilai Sosial Masyarakat - Dozan, Wely (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2020)
This paper tries to discuss social conflict in understanding a tradition of tahlilan where several streams consider that tahlilan is a tradition that was built by the community without being based on hadith texts either in terms of the quality and quantity of the Prophet's hadith. However, some ulama perspectives namely Nahdawtul Ulama) provide the concept of actual tahlilan historically the tradition of tahlilan was born based on the hadith texts of the Prophet according to some narrations of the Companions and the Tabin'in. Specifically, this paper tries to trace the hadith texts among some controversial ideas in understanding the hadith and how the social values ​​contained in the tradition of tahlilan which has always been carried out based on the times. The approach to this paper is the litertaur study approach, namely to explore issues related to both books, journals, articles and so on the results of this study indicate that the traditions of tahlilan traditions that have been carried out there are no restrictions because based on the hadith texts. While in the controversial discourse of thought that prohibits the tradition of tahlilan is still unclear texts of the hadith which has been used as (istinbat) in Islamic law.